LITERASI KEUANGAN, FINANCIAL TECHNOLOGY, DAN MENTAL AKUNTANSI TERHADAP PENGELOLAAN KEUANGAN PADA DRIVER GRAB KOTA BENGKULU - Sari, Nadia Elvita; Baihaqi, Baihaqi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
As informal sector workers, Grab driver Partners face various financial challenges, such as unstable daily income, operational costs, and limited access to financial services. Therefore, understanding financial literacy, financial technology, and accounting can help manage finances effectively. The study aims to see the influence of financial literacy, financial technology, and accounting mentality on financial management. The population studied included all Grab driver partners in Bengkulu City. Convenience sampling was used, and there were 100 respondents. Primary data collection involved distributing questionnaires to Grab driver partners in Bengkulu City. The data analysis tool used SPSS with a multiple linear regression approach. The results of the study showed that financial literacy and accounting mentality have a positive influence on financial management. Financial technology has a negative influence on financial management. This study suggests that an uncertain or fluctuating income pattern in Grab driver partners, balanced by an understanding of financial literacy, financial technology, and accounting mentality, can affect the financial management of Grab driver partners in Bengkulu City to be good or vice versa.